Tolerance of free-living larval stage of a parasite from coastal mining areas in northern Humboldt Current to copper pollution at low and high temperatures. - Natalia V Leiva; Diana Montenegro; Rodrigo Orrego; Rodrigo Vidal; M Teresa González (PLoS ONE)
Metal pollution is a worldwide problem and one of the greatest threats to ecosystem integrity due to its toxicity, persistence, and bioaccumulation in biological systems. Anthropogenic pollution impacts marine organisms and host-parasite dynamics, with the northern Chilean coast experiencing elevated copper levels in marine waters and sediments due to mining activities. In this study, we assessed the effects of exposure to copper concentrations at low and high-water temperatures on the survival and longevity of the marine parasite Himasthla sp. cercariae (Trematoda: Digenea) using the snail Echinolittorina peruviana as its first intermediate host. Snails were collected from intertidal rocky pools in northern Chile (23°S). To assess parasite survival and longevity, cercariae were collected from a pool of infected snails, and their mortality was recorded every 6 hours until all cercariae were dead. In a preliminary experiment conducted at 19°C, cercariae were exposed to different copper concentrations (0.2, 1.5, 3.0, and 6.0 mg/L) for 78 hours. Cercariae showed tolerance to copper. However, at the higher copper concentration (6 mg/L), survival was negatively impacted (50%) at 54 hours. In contrast, at the lower concentration (0.2 mg/L) and in the control group, cercariae sustained a 73-90% survival rate even after 54 hours. Based on these findings, we conducted subsequent experiments involving two copper treatments (0.2 and 3.0 mg/L) and two temperatures (14 and 22°C). Survival and longevity were significantly higher at lower temperature and copper concentration (14°C and 0.2 mg/L). Conversely, at higher temperature and copper concentration (22°C and 3 mg/L), survival and longevity decreased to only 66 hours. Our results show that Himasthla sp. cercariae tolerated most copper concentrations, with vulnerability observed primarily in high water temperatures, indicating an adverse effect on cercariae performance. This study contributes valuable insights into how parasites respond to environmental pollution, in marine ecosystems influenced by anthropogenic activities.